Novel Salicylic Acid Modified Magnetic Nanoparticles Based Ligandless Extraction for the Accurate Determination of Bismuth in Urine Samples by Flame Atomic Absorption Spectrophotometry - Saylan, Meltem; Karlidag, Nazime Ebrar; Toprak, Munevver; Tekin, Zeynep; Balcik, Utku; Er, Elif Ozturk; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2022)
An efficient, novel, rapid and green ligandless dispersive solid phase extraction method (LDSPE) based on salicylic acid modified magnetic iron nanoparticles (SA-MNPs) was combined with slotted quartz tube integrated flame atomic absorption spectrometry (SQT-FAAS) for sensitive bismuth determination in human urine. For this purpose, SA-MNPs were synthesized via a simple procedure and used as sorbent for the effective extraction/preconcentration of bismuth from the aqueous samples. This is the first report in the literature in which this analytical combination (SA-MNPs-LDSPE-SQT-FAAS) was utilized for the determination of bismuth. Under the determined optimum conditions, the linear range was between 20 and 250 mu g L-1. The limit of detection (LOD) and limit of quantification (LOQ) values for bismuth were 6.0 and 21.0 mu g L-1, respectively. A 94-fold enhancement in the detection power of FAAS was achieved using the SA-MNPs-LDSPE-SQT-FAAS method. To examine the method's accuracy and applicability, the optimal procedure was applied to spiked human urine. Satisfactory recoveries from 95% to 101% were obtained with matrix matching, indicating that the developed method can be used for bismuth determination in biological samples.
Keywords: Bismuth; salicylic acid coated magnetic iron nanoparticles; ligandless dispersive solid phase extraction; flame atomic absorption spectrometry; urine; SOLID-PHASE EXTRACTION; COATED FE3O4 NANOPARTICLES; CLOUD POINT EXTRACTION; WATER SAMPLES; PRECONCENTRATION; SPECTROMETRY; CADMIUM; LEAD; NANOTUBES; SORBENT; Chemistry